The correlation between academic stress and emotion regulation - Kasman, Apri; Sagita, Dony Darma; Simarmata, Sari Wardani; Harahap, Ade Chita Putri; Batubara, Azizah; Armitasari, Armitasari; Ritonga, Rahmilawati (Universitas Jambi, Indonesia, 2025)
Academic stress is a common experience among university students and significantly affects their emotional and psychological well-being. Emotion regulation, the ability to manage and respond to emotional experiences, is critical in coping with academic-related stressors. This study examines the correlation between academic stress and emotion regulation strategies among undergraduate students. Using a quantitative correlational design, data were collected from 350 students at Universitas Terbuka through standardized instruments: the Academic Stress Scale (ASS) and the Emotion Regulation Questionnaire (ERQ), which measures cognitive reappraisal and expressive suppression. The results revealed a significant negative correlation between academic stress and cognitive reappraisal, and a significant positive correlation between academic stress and expressive suppression. These findings suggest that students who experience higher levels of academic stress are more likely to engage in maladaptive emotion regulation strategies. The study emphasizes the value of promoting adaptive emotional coping mechanisms to reduce stress and improve students’ academic and mental health outcomes.